Effects of resin content on mechanical properties of cork-based panels bound with melamine-urea-formaldehyde and polyurethane binders. (September 2020) - Antunes, Ana; Pereira, João; Paiva, Nádia; Ferra, João; Martins, Jorge; Carvalho, Luísa; Barros-Timmons, Ana; Magalhães, Fernão D.
Abstract: The properties of agglomerated cork panels bound with melamine-urea-formaldehyde (MUF) and polyurethane (PU) resins were investigated. Tensile strength, Young's modulus, elongation at break, mandrel flexibility, and resistance to boiling water were evaluated. The resins' wettability on the cork surface was also evaluated. The results showed that resin's nature and content influenced significantly the physical-mechanical properties of the agglomerated cork panels. At the same resin content, panels bound with MUF resin presented considerably higher stiffness and tensile strength when compared to panels bound with PU. On the other hand, PU resin lends resilience and water resistance to the panels, and is the only binder that can be used when panel flexibility is desired.